Build on Learners Schema to Teach Mathematics Better (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2016)
Students learn best when the teacher uses a variety of teaching methods. The aim of this conceptual paper is to highlight the need to move from traditional methods to methods which can bring life to the classroom. One way to improve your own teaching is to try to apply schematic learning theory building on learners schema to teach mathemat ics better and then think about how well the activity improved students learning.